A case of juvenile nasopharingeal angiofibroma belonging to the Pathology Museum of Turin. - Ferrari, Luisa (Medicina Historica, 2020)
The Pathology Museum of the University of Turin houses historical dry and wet specimens dating back to the end of XIX and begin of XX century. Among these specimens, a case of juvenile nasopharyngeal angiofibroma was discovered during the study of the diagnostic re-evaluation of the Collection. Juvenile nasopharyngeal angiofibroma is a rare non-capsulated vascular neoplasm predominantly arising in adolescent males. It suggests that this neoplasia could be androgen dependent, but this hypothesis remains controversial and its origin is still not clear. It is considered a benign neoplasm but locally aggressive and it could spread to the base of the skull and into the cranium. The museum wet-specimen dates back to March 31th 1911, as shown on the autopsy report which number is reported on the original label on the jar. The specimen was collected performing the autopsy on a 14years old boy who died of unknown reasons, most likely for epistaxis or suffocation. The only pathological finding is the nasopharyngeal lesion. Macroscopic examination of the specimen shows that on the base of the skull there is a huge polypoid lesion. Histopathology shows an edematous fibrous stroma and staghorn blood vessels irregular in size and shape. The tissue appears to be well preserved despite the long extended period in fluid. The original diagnosis was “Nasopharyngeal polyp” and it was actually the name of juvenile nasopharyngeal angiofibroma before the first official report of this lesion in the year 1948.